Spectrophotometric Methods for Measurement of Antioxidant Activity in Food and Pharmaceuticals - Marios C. Christodoulou; Jose C. Orellana Palacios; Golnaz Hesami; Shima Jafarzadeh; José M. Lorenzo; Rubén Domínguez; Andres Moreno; Milad Hadidi (MDPI AG, 2022)
In recent years, there has been a growing interest in the application of antioxidants in food and pharmaceuticals due to their association with beneficial health effects against numerous oxidative-related human diseases. The antioxidant potential can be measured by various assays with specific mechanisms of action, including hydrogen atom transfer, single electron transfer, and targeted scavenging activities. Understanding the chemistry of mechanisms, advantages, and limitations of the methods is critical for the proper selection of techniques for the valid assessment of antioxidant activity in specific samples or conditions. There are various analytical techniques available for determining the antioxidant activity of biological samples, including food and plant extracts. The different methods are categorized into three main groups, such as spectrometry, chromatography, and electrochemistry techniques. Among these assays, spectrophotometric methods are considered the most common analytical technique for the determination of the antioxidant potential due to their sensitivity, rapidness, low cost, and reproducibility. This review covers the mechanism of actions and color changes that occur in each method. Furthermore, the advantages and limitations of spectrophotometric methods are described and discussed in this review.